Darwin's Legacy: The Peacock Paradox (London Journal of Research In Science: Natural and Formal, 2024)
The foundation of this paper is the generation of all life by evolution. By this as- sumption, everything has to be compatible with Darwins theory. I discuss some issues that concern animate beings. I ask some rhetorical questions. Answers are provided by speculations. I present arguments for an evolution and general thoughts. I show that some properties of animate beings are compatible with an evolution. The arguments except those in the chapter Homosexuality are ideas of mine. All points only are personal views.
Keywords: Solanaceae; Solanum boldoense Dunal & A.DC; Steroidal compounds.; Ozone-depleting substances; Illegal trade; Montreal Protocol; Environ- mental protection; Ozone layers; Skin cancer; blindness.